2009
DOI: 10.1271/bbb.80391
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile in the Anterior Regeneration of the Earthworm Using Expressed Sequence Tags

Abstract: In order to gain insight into the gene expression profiles associated with anterior regeneration of the earthworm, Perionyx excavatus, we analyzed 1,159 expressed sequence tags (ESTs) derived from cDNA library early anterior regenerated tissue. Among the 1,159 ESTs analyzed, 622 (53.7%) ESTs showed significant similarity to known genes and represented 338 genes, of which 233 ESTs were singletons and 105 ESTs manifested as two or more ESTs. While 663 ESTs (57.2%) were sequenced only once, 308 ESTs (26.6%) appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
15
1
1
Order By: Relevance
“…Coelomocyte hematopoiesis following severe blood loss (exsanguination) in the peanut worm, Phascolosoma esculenta , accompanies the de novo synthesis of Hr [53]. Isoforms of Hr and myoHr have also been found in the salivary complex of the hematophagous leech, Haementeria depressa, and during anterior tissue regeneration of the earthworm, Perionyx excavatus [197, 198]. These data signify Hr is a multi-functional protein extending beyond its traditional role as a vehicle for molecular oxygen.…”
Section: Hemerythrin and Innate Immunitymentioning
confidence: 99%
“…Coelomocyte hematopoiesis following severe blood loss (exsanguination) in the peanut worm, Phascolosoma esculenta , accompanies the de novo synthesis of Hr [53]. Isoforms of Hr and myoHr have also been found in the salivary complex of the hematophagous leech, Haementeria depressa, and during anterior tissue regeneration of the earthworm, Perionyx excavatus [197, 198]. These data signify Hr is a multi-functional protein extending beyond its traditional role as a vehicle for molecular oxygen.…”
Section: Hemerythrin and Innate Immunitymentioning
confidence: 99%
“…Such expression polarity toward energy metabolism showed higher as twice as that of the midgut in the same earthworm species. 24) Considered that in the gene expression profiling analysis using EST, the highly expressed genes would reflect the prime functions of the analyzed tissues or cell types, [28][29][30][31] the primary function of coelomic cells in the earthworm might be associated with high energyconsuming functions including immune responses. In particular, among the 12 most highly expressed genes, the high frequency (2.87%) of no-matched genes possibly representing novel genes could address the new functions of earthworm coelomic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Subtractive hybridization experiments in regenerating fragments of Enchytraeus japonensis revealed that novel genes (which are not represented in other phyla or even the Lumbricus rubellus) were upregulated in regenerative processes hinting towards the involvement of annelid specific genes in regeneration 87 . Gene expression profiling in anterior regenerating segments of Perionyx excavatus also yielded several novel ESTs, involved in regeneration 88 . Transcriptomic analysis of a mixed-stage sample of regeneration and fission in has also been recently attempted 89 .…”
Section: Discussionmentioning
confidence: 99%